Sikap dan Efikasi Diri Lansia Berhubungan Dengan Keaktifan Kunjungan Posbindu Pada Penderita Hipertensi di Wilayah Kerja Puskesmas Sidoharjo, Sragen : Sikap dan Efikasi Diri Lansia Berhubungan Dengan Keaktifan Kunjungan Posbindu Pada Penderita Hipertensi di Wilayah Kerja Puskesmas Sidoharjo, Sragen - Tidi Orchida; Mulyaningsih (Jurnal Keperawatan Duta Medika, 2023)
Introduction: The elderly population continue to increase. Health is a state of health, both physically, mentally, spiritually, and socially that allows everyone to live a socially productive life. HypertFDXCension is a major health problem in developed and developing countries, hypertension is a non-communicable disease and is the number one cause of death globally Objectives: To determine the effect of the relationship between attitudes and self-efficacy with the activeness of posbindu visits to patients with hypertension in the working area of ​​the Sidoharjo Health Center, Sragen Methods: This type of research was quantitative, this research method used cross sectional. Sampling of 65 respondents. The research instrument used a closed questionnaire. Data analysis using Chi square test. Results: The results showed a positive relationship between self-efficacy and activity with p value 0.013 with an OR value of 10.6. Attitude and activity also show a positive relationship as evidenced by the p value of 0.005 and the OR value of 21.6 Conclusions:  There was a significant relationship between attitude and self-efficacy with the activeness of Posbindu visits in patients with hypertension in the work area of ​​the Sidoharjo Health Center, Sragen.